2020
DOI: 10.1007/s12031-020-01543-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Expression of SNAP-25 Protein in the Brain of Juvenile Rats in Two Models of Autism

Abstract: The results of genetic studies suggest a possible role for SNAP-25 polymorphism in the development of autism spectrum disorders (ASDs); however, there are no data available on whether changes in SNAP-25 expression also affect animals in rodent models of ASD. The aim of the present study was to explore this issue. The studies included 1-month-old rats representing valproic acid (VPA)-and thalidomide (THAL)-induced models of autism. Their mothers received single doses of VPA (800 mg/kg) or THAL (500 mg/kg) per o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
1
4
1
Order By: Relevance
“…Opposite results were obtained according to the exposure to VPA (16% decrease) or to α-HBCDD (19% increase, p = 0.082) compared to controls, thus inducing a 30% difference between these two groups (p = 0.082). A decrease in SNAP25 in the frontal lobe of the animals in the VPA model has already been reported [48]. In parallel, the results obtained for α-HBCDD are consistent with those observed for tetrabromobisphenol-A (TBBPA; another flame retardant), for which an increase in SNAP25 was observed after in-vitro exposure of primary rat cerebellar granule cell cultures [49].…”
Section: Neuroglia and Synaptic Plasticity In The Cortexsupporting
confidence: 83%
“…Opposite results were obtained according to the exposure to VPA (16% decrease) or to α-HBCDD (19% increase, p = 0.082) compared to controls, thus inducing a 30% difference between these two groups (p = 0.082). A decrease in SNAP25 in the frontal lobe of the animals in the VPA model has already been reported [48]. In parallel, the results obtained for α-HBCDD are consistent with those observed for tetrabromobisphenol-A (TBBPA; another flame retardant), for which an increase in SNAP25 was observed after in-vitro exposure of primary rat cerebellar granule cell cultures [49].…”
Section: Neuroglia and Synaptic Plasticity In The Cortexsupporting
confidence: 83%
“…In our previous works (Lenart et al, 2020b;Toczylowska et al, 2020), we did not find significant statistical differences between males and females within the study group. Therefore, we decided to perform our first screening test of genes encoding proteins of selected receptors, involved in the pathogenesis of ASD, on males, in which we observed slightly greater changes than in females.…”
Section: Gene Expression Analysis (Rt-qpcr)contrasting
confidence: 63%
“…The resulting network suggested that SCGN regulated the oxytocin and the immune response pathways via SNAP-25, whose abnormal expressions and/or mutations have been associated with ASD and other neurological disorders. 16 We found that 24 genes, including Camk2b, Adcy5, Cacna2d3, Camk2a, Itpr1, Plcb1, Prkcb, Mef2c , and Ptgs2 , were ASD-risk genes that were involved in the oxytocin pathway. Among them, CAMK2A and CAMK2B are Calcium/calmodulin-dependent protein kinase II (CaMKII) isoforms with pivotal roles in neuronal development.…”
Section: Resultsmentioning
confidence: 78%
“…In recent years, studies including genome-wide sequencing technologies have revealed a large set of ASD-risk genes, [11][12][13][14] which are often associated with a number of biological functions/pathways, including synaptic structure and functions (e.g., SNAP-25, STXBP2, SHANK3, and NLGN3), chromatin modification (e.g., CHD7 and MECP2), Wnt signaling (e.g., CHD8, PAX5, and ATRX), oxytocinergic signaling, immune function, and mitochondrial function, among other processes. 2,[15][16][17] One emerging concept in the field is that these pathways could converge on the regulation of a few key functional activities. For instance, the loss of synaptic adhesion molecule Nlgn3 impairs oxytocin signaling and disrupts normal translation.…”
Section: Introductionmentioning
confidence: 99%